Biomechanical Study Examining the S2 Alar Iliac Screw Insertional Torque. Issue 1 (April 2016) - Ledonio, Charles; Donguyen, Huy; Santos, Edward; Sembrano, Jonathan; Morgan, Robert; Polly, David
Introduction: Prior biomechanical studies have examined the role of the iliac screw in lumbosacral fixation [Lebwohl, 2002; Cunningham, 2010] and while found to be significant, the ideal screw device and fixation technique have yet to be identified. An initial effort to define this biomechanical fixation includes measurements of current screw insertion torque across screw length was developed. The objective of this study was to measure the intraoperative torque required to place an S2-Alar iliac screw for spino-pelvic fixation. This fixation method often results in variable screw fixation strength and an improved understanding of the local torques required along the length of the screw will aid in improving this surgical fixation. Materials and Methods: This IRB approved study involves obtaining informed consent of patients receiving long spinal fusions either for adult deformity. The surgical trajectory for the S2-Iliac screw will be identified as is currently practiced using O-arm Stealth Navigation. Next, the insertion torque of the iliac screw will be measured using the standard driver handle fitted with a torque cell sensor by the surgeon under 3D navigation (Stealth). Results: There were 6 patients who underwent spino-pelvic fixation. 12 S2-Iliac screws were placed however Insertional torque was recorded in only 6 screws. Screw maps show that peak torques range from 0.71 to 9.73 Nm. Highest torques recorded were when the head of the screw approached the bone during insertion. These peak torques recorded are 1.91 times higher than Iliac screw insertional torques reported in a previous study. Conclusion: Peak insertional torques range from 0.71 to 9.73 Nm and occurred as head of the screw approached the bone during insertion. However higher insertional torques were not recorded because it went beyond the capacity of the driver.